2021
DOI: 10.20886/ijfr.2021.8.2.127-134
|View full text |Cite
|
Sign up to set email alerts
|

BIOACTIVITY ANALYSIS OF Annona glabra L. SEED EXTRACTS FOR WOOD PROTECTION AGAINST TERMITES (Cryptotermes cynocephalus Light. AND Coptotermes curvignathus Holmgren.)

Abstract: Pond apple (Annona glabra L.) belongs to the family of Annonaceae. The seed of A. glabra contains bioactive substance that is toxic to some organisms, however the effectiveness to control wood degrading termites has not yet been scientifically reported.  This research analyzes the efficacy of A. glabra seed extract to wood degrading termites. Seed extraction was conducted using n-hexane and ethyl acetate. The paper disc test showed that the extract of A. glabra is toxic to Cryptotermes cynocephalus (dry-wood t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…The probit analysis (Table 2) showed the LC50 value of 2.38 with a fiducial limit of about 2.03-2.80 and 3.06 % with a fiducial limit of about 2.58-3.64 for O. anamallensis and M. fletcheri respectively. Trisna Priadi et al [14] reported that the A. glabra extract showed insecticidal activity against wood-destroying termites Cryptotermes cynocephalus (dry-wood termites) and Coptotermes curvignathus. Sini et al [15] reported that the A. squamosa L. extract, which contains octadecenoic acid (oleic acid), showed insecticidal activity against the insects.…”
Section: Toxicity Of Petroleum Ether Extract Of a Squamosa Seedsmentioning
confidence: 99%
“…The probit analysis (Table 2) showed the LC50 value of 2.38 with a fiducial limit of about 2.03-2.80 and 3.06 % with a fiducial limit of about 2.58-3.64 for O. anamallensis and M. fletcheri respectively. Trisna Priadi et al [14] reported that the A. glabra extract showed insecticidal activity against wood-destroying termites Cryptotermes cynocephalus (dry-wood termites) and Coptotermes curvignathus. Sini et al [15] reported that the A. squamosa L. extract, which contains octadecenoic acid (oleic acid), showed insecticidal activity against the insects.…”
Section: Toxicity Of Petroleum Ether Extract Of a Squamosa Seedsmentioning
confidence: 99%
“…In the genus Annona, the species Annona glabra, A. hypoglauca, A. montana and A. squamosa are included for their known insecticidal and acaricidal potential on Tetranychus urticae (Acari: Tetranychidae) (Maciel et al, 2019); Cryptotermes cynocephalus and Coptotermes curvignathus (Priadi et al, 2021); and, on the aphids, A. craccivora (Rabelo & Bleicher, 2014) and A. gossypii (Santos et al, 2018). Contribuciones a Las Ciencias Sociales, São José dos Pinhais, v.16, n.12, p. 32146-32160, 2023 Knowing this, this study proposed to evaluate the toxicity and repellency of aqueous extracts of A. glabra, A. hypoglauca, A. montana and A. squamosa leaves, obtained from the Amazonian savanna of Roraima, Brazil, on A. craccivora (Hemiptera: Aphididae), under laboratory conditions.…”
Section: Introductionmentioning
confidence: 99%